Comparison of the Use of Conceptual Blending in Literary and Scientific Writing Styles - Hossein Razavian; Seyyed Hamzeh Mousavi; Shaghayegh Khaki (مطالعات زبانی و بلاغی)
One of the important topics in cognitive linguistics is conceptual blending, which creatively combines two distinct concepts and has been used to explain literary structures. In this article, we demonstrate that the use of conceptual blending is not only for creating imaginative sentences; sometimes, if the genre changes, the type and structure of conceptual blending change accordingly. To examine the impact of genre on types of blending, two books by Sirūs Shamisā, Monsoon (as an example of a literary text) and Literary Criticism (as an example of a scientific text), were selected, and sentences containing conceptual blending were extracted. Ultimately, we found that the data from Monsoon, which are literary in nature, are used to create imaginative scenes and sometimes blend with mythological characters and events, while in Literary Criticism, blending is related to concrete phenomena and events that lead to a clearer understanding of scientific content. Therefore, the literary genre makes the blendings abstract and the scientific genre concretize them. Additionally, it was concluded that Monsoon is a type of macro blending; the entire story is blended with its title, and the plot of the story is blended with the Monsoon storm.